2021
DOI: 10.3138/jvme.2019-0006
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Impact of Using a Simulator for Teaching Veterinary Students Cerebrospinal Fluid Collection: A Mixed-Methods Study

Abstract: The collection of cerebrospinal fluid (CSF) plays a pivotal role in the diagnosis of central nervous system diseases. Prior training in this invasive procedure is essential to minimize the risk of harming animals. Because of this risk, stress and anxiety can influence the learning process. Simulators can be used to teach and learn invasive procedures. The aim of this mixed-methods study was to validate a CSF collection simulator and investigate students’ perceptions of the simulator as an educational tool. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 25 publications
1
12
0
1
Order By: Relevance
“…65,84 Simulators have also been shown to decrease student anxiety prior to performing a task on a live animal. 56,71,82…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…65,84 Simulators have also been shown to decrease student anxiety prior to performing a task on a live animal. 56,71,82…”
Section: Discussionmentioning
confidence: 99%
“…The study 37 appeared to show that simulations can be an effective supplement to traditional teaching methods, but it seems that, alongside some academics (as documented by Knight 90 ), some students still prefer live-animal or cadaver practical classes. 56 The preference for live-animal classes amongst some students could be due to increased realism and the perception that simulators cannot provide a true representation of performing tasks on live patients, even if the learning outcomes achieved through the use of simulators have been documented to be equivalent or superior to those achieved by using live animals. 91 More research is required on this topic, particularly in light of recent advancements and growth in the area of simulators and simulations for use within veterinary education.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7 Recent studies have demonstrated that training on simulators can improve students' confidence, performance and learning ability, across a number of practical veterinary skills. [8][9][10][11][12][13][14][15][16] Furthermore, recent meta-analyses have found that learning outcomes and proficiency are equivalent or greater in veterinary students taught using simulators versus those taught with traditional teaching models. 5,6 However, a significant challenge in simulator design is the ability to accurately replicate the physical and functional characteristics of a living patient.…”
Section: Introductionmentioning
confidence: 99%